In Vivo Inflammation Does Not Impair ABCA1-Mediated Cholesterol Efflux Capacity of HDL. (24th April 2012) - Franssen, Remco; Schimmel, Alinda W. M.; van Leuven, Sander I.; Wolfkamp, Simone C. S.; Stroes, Erik S. G.; Dallinga-Thie, Geesje M.
Abstract : HDL provides atheroprotection by facilitating cholesterol efflex from lipid-laden macrophages in the vessel wall. In vitro studies have suggested impaired efflux capacity of HDL following inflammatory changes. We assessed the impact of acute severe sepsis and mild chronic inflammatory disease on the efflux capacity of HDL. We hypothesize that a more severe inflammatory state leads to stronger impaired cholesterol efflux capacity. Using lipid-laden THP1 cells and fibroblasts we were able to show that efflux capacity of HDL from both patients with severe sepsis or with Crohn's disease (active or in remission), either isolated using density gradient ultracentrifugation or using apoB precipitation, was not impaired. Yet plasma levels of HDL cholesterol and apoA-I were markedly lower in patients with sepsis. Based on the current observations we conclude that inflammatory disease does not interfere with the capacity of HDL to mediate cholesterol efflux. Our findings do not lend support to the biological relevance of HDL function changes in vitro .